The immigrant/native wealth gap in Germany, Italy and Luxembourg - Thomas Y. Mathä; Alessandro Porpiglia; Eva Sierminska (European Central Bank (ECB), 2011)
This paper analyses the existence of an immigrant/native wealth gap by using household survey data for Luxembourg, Germany and Italy. The results show that, in all three countries, a sizeable wealth gap exists between natives and immigrants. Towards the upper tail of the wealth distribution the gap narrows to a small extent. This gap persists even after controlling for demographic characteristics, country of origin, cohort and age at migration although cross-country differences exist in the immigration penalty.
Keywords: D31; F22; 330; distribution; household; immigrants; survey data; wealth gap